2021
DOI: 10.1002/ar.24710
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effect and mechanism of Fu's subcutaneous needling among patients with shoulder pain: A retrospective pilot study

Abstract: Fu's subcutaneous needling (FSN) is a new acupuncture therapy developed from acupuncture and Traditional Chinese Medicine models. The aim of this study was to investigate the effect of FSN on shoulder pain. In this retrospective comparative study, patient case files with shoulder pain (Group A) treated with FSN were analyzed and compared with the same number of patients with shoulder pain (Group B) treated with conventional acupuncture and physical therapy. Motion-related

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Various interventions such as therapeutic exercise, cognitive behavioral approach, and acupuncture therapy have been developed to reduce shoulder pain. [21][22][23] If the interventions can be customized for suitability to each specific subject, these will be effective in reducing shoulder pain and shoulder disability.…”
Section: Discussionmentioning
confidence: 99%
“…Various interventions such as therapeutic exercise, cognitive behavioral approach, and acupuncture therapy have been developed to reduce shoulder pain. [21][22][23] If the interventions can be customized for suitability to each specific subject, these will be effective in reducing shoulder pain and shoulder disability.…”
Section: Discussionmentioning
confidence: 99%
“…[7] FSN treatment has been shown to have efficacy in several musculoskeletal disorders. [8,9] Immediately after FSN intervention, a reexamination of the VA using the CVA ultrasound revealed that the luminal diameter of the right VA was 2.7 mm (Fig. 1B), which was 0.6 mm wider.…”
Section: Casementioning
confidence: 99%
“…[1][2][3] FSN therapy is widely used, and its efficacy is exact for somatic and visceral pain; it also has remarkable effects on nonpainful conditions, such as chronic bronchitis, stress urinary incontinence, chronic superficial gastritis disease, Parkinson's disease, myopia, and intractable diarrhea, but its specific mechanism of action is yet to be elucidated. [4][5][6] The diseases that FSN can treat, including painful or non-painful diseases, are initially caused by muscle problems. Longterm muscle overload, exercise, incorrect force posture, and muscle atrophy and degeneration lead to ischemia and hypoxia of muscle tissues and cause myofascial trigger point (MTrP) via the theory of energy crisis.…”
Section: Introductionmentioning
confidence: 99%